Aerogel composite
Patent Information
- Application Number
- KR1020250063626
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-11-14
- Filing Date
- 2025-05-16
- Publication Date
- 2026-09-09
- Estimated Expiration
- 2045-05-16
Smart Images

Figure 1020250063626
Abstract
Description
Technology Field
[0001] The present invention relates to an aerogel, an aerogel composite, and its application as an insulating material. Background Technology
[0002] Aerogels are ultraporous materials with a high specific surface area (≥500 m²) having a porosity of approximately 90.0% to 99.9% and a pore size in the range of 1 nm to 100 nm. 2 As a material with a g content, it is a material possessing excellent properties such as ultralight weight, ultra-insulating insulation, and ultra-low dielectric strength. Accordingly, active research is being conducted not only on the development of aerogel materials but also on their application as transparent and eco-friendly high-temperature insulating materials, ultra-low dielectric thin films for high-density integrated devices, catalysts and catalyst supports, electrodes for supercapacitors, and electrode materials for seawater desalination.
[0003] The biggest advantage of aerogel is that it has super-insulation properties with a thermal conductivity of 0.300 W / m·K or less, which is lower than conventional organic insulation materials such as styrofoam, and it can solve the fatal weaknesses of organic insulation materials, such as fire vulnerability and the generation of harmful gases during a fire.
[0004] Aerogel blankets, in which aerogel is formed on fibers, are widely used in construction or industrial sites as functional thermal insulation materials. Additionally, they can be usefully employed as insulation, thermal insulation, or non-combustible materials for aircraft, ships, automobiles, batteries, and more.
[0005] Meanwhile, these aerogel blankets are manufactured by preparing a silica sol from silica precursors such as water glass and alkoxysilane series (TEOS, TMOS, MTMS, etc.), mixing fibers into the sol to gel it, and then aging, surface modification, and drying.
[0006] If the entire aerogel blanket is not sufficiently hydrophobized during the above-mentioned process, hydrophobic groups, such as methyl or ethyl groups, on the surface of the aerogel or inside the pores will burn up during atmospheric drying, causing a loss of hydrophobicity. This results in a decrease in thermal insulation performance due to moisture penetration, as well as a permanent loss of thermal insulation performance due to the collapse of the pore structure caused by shrinkage during the evaporation process of the penetrated moisture.
[0007] Therefore, in order to utilize aerogel blankets as insulation materials, it is important to maintain high hydrophobicity by ensuring that hydrophobic groups are stably present not only on the surface but also within the pores, thereby preventing the deterioration of insulation performance. The problem to be solved
[0008] One objective of the present invention is to provide an aerogel composite or an insulating member containing the same, wherein hydrophobic groups within the pores of the aerogel composite can stably exist and maintain high hydrophobicity even when the aerogel composite is exposed to a high-temperature environment such as atmospheric pressure drying.
[0009] However, the technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem
[0010] According to one embodiment of the present invention, an aerogel composite comprises a fiber substrate; and an aerogel having a plurality of open pores, wherein the aerogel comprises a plurality of silica aerogel particles, and as a result of performing NMR analysis on the aerogel particles using water (H2O) as the saturation fluid, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) is 0.4 x 10⁻⁶ 3 Up to 1.0 X 10 3 Or, 0.4 X 10 3 Up to 0.9 X 103 It could be.
[0011] As a result of performing NMR analysis using water (H2O) as the saturation fluid after heat-treating the aerogel particles separated from the above aerogel composite at 200°C for 1 hour, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) was 0.4 X 10⁻⁶ 3 Up to 1.0 X 10 3 It could be.
[0012] In addition, after heat-treating the aerogel particles separated from the aerogel composite at a temperature of 200°C for 1 hour, the T1 / T2 ratio may be 0.8 to 1.2 times, or 0.85 to 1.1 times, compared to the T1 / T2 ratio of the aerogel particles before heat treatment.
[0013] The above aerogel may contain pores with a pore diameter of 5 to 20 nm or less in an amount of 25% or less of the pore volume of the skeletal structure, or 10% or more and 25% or less.
[0014] The above aerogel composite may have a moisture impregnation rate (weight%) represented by Formula 1 below of 4 weight% or less. However, in the formula below, the weight of the specimen after impregnation refers to the weight of the aerogel composite specimen after impregnating it in distilled water at 21±2 ℃ for 15 minutes, and the specimen has dimensions of 100 mm x 100 mm in width x length.
[0015] [Equation 1]
[0016] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100
[0017] However, in the case where the width X length of the specimen used in the experiment in Formula 1 above is 10 mm X 10 mm, the moisture impregnation rate (weight%) of the aerogel composite may be 3 weight% or less.
[0018] In addition, the moisture impregnation rate (weight%) represented by Formula 1 above may be 10 weight% or less after heat treatment of the above aerogel composite at a temperature of 200 ℃ for 1 hour.
[0019] The above aerogel composite may have a water vapor absorption rate of 2.5 weight% or less according to the ASTM C1104 test method.
[0020] The above aerogel may include one or more selected from the group consisting of silica, methylsilylated silica, dimethylsilylated silica, and trimethylsilylated silica.
[0021] The plurality of aerogel particles may include particles formed by aggregation or bonding of a plurality of aerogel particles having a particle size greater than 0 and less than or equal to 5 nm. In this case, the average particle size of the aggregated or bonded aerogel particles may be 5 to 2,000 nm.
[0022] The thickness of the above aerogel composite may be 0.1 to 20 mm.
[0023] The density of the above aerogel composite is 0.05 to 0.50 g / cm³ 3 It could be.
[0024] The above aerogel composite has a compressive strength of 20 kPa to 80 kPa at 10% strain and a tensile strength of 30 N / cm 2 up to 60 N / cm 2 It could be.
[0025] According to another embodiment of the present invention, the invention relates to an aerogel comprising a plurality of open pores and a plurality of silica aerogel particles, wherein NMR analysis was performed on the aerogel particles using water (H2O) as the saturation fluid, and the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) is 0.4 x 10⁻⁶ 3 Up to 1.0 X 10 3 Or, 0.4 X 10 3 Up to 0.9 X 103 It could be.
[0026] As a result of performing NMR analysis using water (H2O) as the saturation fluid after heat-treating the above aerogel particles at a temperature of 200 ℃ for 1 hour, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) was 0.4 X 10⁻⁶ 3 Up to 1.0 X 10 3 It could be.
[0027] In addition, after heat-treating the aerogel particles at a temperature of 200°C for 1 hour, the T1 / T2 ratio may be 0.8 to 1.2 times, or 0.85 to 1.1 times, compared to the T1 / T2 ratio of the aerogel particles before heat treatment.
[0028] According to another embodiment of the present invention, the invention relates to an insulating member comprising the aerogel composite.
[0029] The above insulating member may further include a support member located on at least one of the upper and lower surfaces of the aerogel composite.
[0030] According to another embodiment of the present invention, the invention relates to a battery module comprising a module case including an internal space and one or more battery cells located in the internal space, wherein the aerogel composite described above may be located in the internal space.
[0031] According to another embodiment of the present invention, the invention relates to a battery pack comprising the battery module described above. Effects of the invention
[0032] The aerogel composite provided in the present invention has a high degree of hydrophobicity even within the pores of the aerogel matrix and excellent pore strength, so that pore shrinkage is minimized and high thermal insulation can be maintained even when an atmospheric pressure drying process is performed during the manufacturing process of the aerogel composite or when the manufactured aerogel composite is exposed to a high-temperature environment. Specific details for implementing the invention
[0033] Hereinafter, the present invention will be described in more detail to aid in understanding the invention. In this case, terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.
[0035] According to one embodiment of the present invention, the invention relates to an aerogel composite comprising a fiber substrate; and an aerogel having a plurality of open pores.
[0036] The above "aerogel" comprises a plurality of primary aerogel particles having a size of approximately greater than 0 and less than 10 nm, greater than 0 and less than 5 nm, and secondary aerogel particles formed by aggregation or bonding of these primary aerogel particles, and as a plurality of open pores are formed between the primary aerogel particles and between the secondary aerogel particles to form aggregates, the aerogel forms a three-dimensional network structure.
[0037] The above aerogel may be an inorganic silica aerogel formed from a silicon alkoxide-based compound or water glass as a precursor. As an example, the above aerogel may be composed of silica, methylsilylated silica, dimethylsilylated silica, trimethylsilylated silica, or a mixture thereof. As another example, the above aerogel may have at least some of the SiO2 on the surface of the SiO2 network structure having a bonding structure of Si-O-SiO2(CH3), Si-O-SiO(CH3)2, or Si-O-Si(CH3)3. The specific manufacturing process of the silica aerogel is described in detail below.
[0038] Aerogel particles may be located on the fiber substrate and in the voids between adjacent fiber substrates. The "aerogel particles" are particles in the form of individual solid units constituting the aerogel, and may include primary aerogel particles having a size of approximately greater than 0 and less than 10 nm, greater than 0 and less than 5 nm, or around 1 nm, and secondary aerogel particles formed by the aggregation of these particles. However, the aerogel within the aerogel composite may mostly consist of secondary aerogel particles or a form in which they are aggregated and bonded, and a small amount of primary aerogel particles that do not form secondary aerogel particles may be mixed in. The secondary aerogel particles may have an average particle size of approximately 5 to 2,000 nm, 5 to 1,000 nm, 5 to 500 nm, 5 to 100 nm, or 5 to 50 nm, but are not limited thereto. The above average particle size may be measured by any means known to those skilled in the art, such as scanning electron microscopy, dynamic light scattering, optical microscopy, or size exclusion methods, but is not limited thereto.
[0039] The aerogel may have a matrix framework structure including mesopores, and may include micropores or macropores in addition to the mesopores. Here, the "mesopore" is a pore with an average pore diameter in the range of about 2 nm to about 50 nm, the "macropore" is a pore with an average pore diameter exceeding about 50 nm, and the "micropore" is a pore with an average pore diameter less than about 2 nm. The aerogel may contain at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 96%, at least 97%, at least 98%, at least 99%, or 100% mesopores of the pore volume of the framework structure. In one embodiment, the aerogel may include mesopores. In one specific example, the aerogel may include mesopores and micropores. The pore size may be measured by any means known to those skilled in the art, such as gas adsorption experiments, mercury infiltration, capillary flow porometry, or positron annihilation lifetime spectroscopy (PALS), but is not limited thereto.
[0040] The above-described aerogel composite has a structure in which at least some of a plurality of aerogel particles are dispersed, preferably bonded, on the surface of a substrate containing fibers, and at the same time, at least some of a plurality of aerogel particles are dispersed, preferably located, in the empty spaces between the discrete fibers within the substrate. Examples of the substrate may be discrete fibers, films, sheets, nets, fibers, porous bodies, foams, nonwoven fabrics, or laminates of two or more layers thereof. Additionally, depending on the application, the surface may have a surface roughness or be patterned.
[0041] The above fiber substrate is polyester, polyolefin terephthalate, poly(ethylene) naphthalate, polycarbonate (e.g., rayon, nylon), cotton (e.g., Lycra from DuPont), carbon (e.g., graphite), polyacrylonitrile (PAN), PAN oxide, non-carbonized heat-treated PAN (e.g., from SGL Carbon), glass fiber-based materials (S-glass, 901 glass, 902 glass, 475 glass, E-glass, etc.), silica-based fibers, e.g., quartz (e.g., Saint-Gobain Quartzel), Q-felt (from Johns Manville), Saffil, Durablanket (from Uniplex), or other silica fibers, Duraback (from carborundum), polyaramid fibers, e.g., Kevlar, Nomex, or Sontera (all from DuPont), Conex (from Tyzine), polyolefins, e.g., Tyvek (from DuPont), Dyneema (from DSM), Spectra (made by Honeywell), other polypropylene fibers such as Typar and Xavan (both made by DuPont), fluoropolymers such as PTFE under the brand name Teflon (made by DuPont), Goretex (made by WL GORE), silicon carbide fibers such as Nicalcon (made by COI Ceramics), ceramic fibers such as Nextel (made by 3M), ceramic paper, acrylic polymers, wool, silk, hemp, leather, suede fibers, PBO-Xylon fibers (made by Tyobo), liquid crystal materials such as Vectan (made by Hoechst), Cambrel fibers (made by DuPont), polyurethane, polyamide, wool fibers, basalt fibers, boron, aluminum, iron, stainless steel fibers, or other thermoplastic resins such as PEEK, PES, PET, PEK, PPS, etc., but any fiber that can further improve thermal insulation performance by including a space or void where the insertion of aerogel is easy can be used without limitation. For example, the fiber substrate may include glass fibers, basalt fibers, or ceramic paper.
[0042] The thickness of the fiber substrate may be 0.1 to 20 mm, but is not limited thereto.
[0043] In addition, the thickness of the aerogel composite may be 0.1 to 20 mm, but is not limited thereto.
[0044] Generally, in the manufacturing of aerogel composites, hydrophobicity is imparted to the composite through a surface modification process to prevent the degradation of thermal insulation performance caused by moisture penetration when the aerogel composite is applied as an insulating material. However, only when sufficient hydrophobicity is achieved not only on the surface of the aerogel composite but also within the pores inside the aerogel matrix, and when the pores possess excellent elasticity and strength, can the aerogel composite maintain high hydrophobicity and thus maintain excellent thermal insulation performance even when exposed to high-temperature environments.
[0045] In relation to this, nuclear magnetic resonance spectroscopy (NMR) analysis was performed to analyze the structural characteristics of the pores included in the aerogel composite of the present invention, particularly the aerogel matrix, and the degree of hydrophobization inside the pores.
[0046] In the present invention, the above-mentioned NMR analysis uses 600 MHz NMR to analyze non-zero magnetic moments of hydrogen atoms ( 1H) is detected and performed through spectroscopic measurements, relaxation method measurements, diffusion measurements, or imaging measurements. NMR signals of the fluid within the pores of the sample and the fluid outside the sample can be detected. In this invention, T1 relaxation time and T2 relaxation time were obtained through NMR analysis to confirm the characteristics of the pores within the aerogel matrix constituting the aerogel composite or the aerogel particles forming it. Here, the "T1 relaxation time" is also referred to as "longitudinal relaxation time" or "spin-lattice relaxation time." The T1 relaxation time can be obtained by an "inversion recovery method," which involves squelching by appropriately applying a sufficiently strong RF pulse or actually reversing the magnetization. "T2 relaxation time," also known as transverse relaxation time or spin-spin relaxation time, is determined by the interaction between the molecular characteristics of the saturated fluid within the sample's pores and the pore network structure. T2 relaxation time can be obtained using the CPMG (Car-Purcell-Meiboom-Gill) echo sequence. The movement of fluid saturated within the sample's pores is more restricted than that of fluid molecules in a typical bulk state due to structural and chemical interactions within the confined space of the pores; this results in a reduction of both T1 and T2 relaxation times. In particular, T2 relaxation time is significantly influenced by the interaction between the molecular characteristics of the saturated fluid within the pores and the pore network structure. However, if paramagnetic components are present in the sample, the values of T1 and T2 relaxation times decrease significantly, but in this case... 1The H T1 / T2 ratio remains at a similar value regardless of the concentration of paramagnetic components (RSC Adv., 2017, 7, 36163-36167). That is, since the T1 / T2 ratio reflects only internal pore information excluding paramagnetic effects, the present invention aims to determine pore characteristics regardless of the presence or absence of paramagnetic materials in the aerogel sample. 1 Information regarding the pores was obtained using the H T1 / T2 ratio value. Furthermore, in this invention, water (H2O) was used as the saturation fluid to determine not only the internal structural characteristics (size, complexity, etc.) of the pores but also the degree of hydrophobicity within the pores during NMR analysis.
[0047] As a result of performing NMR analysis on the aerogel particles included in the aerogel composite of the present invention using water (H2O) as the saturation fluid, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) was 0.4 X 10 3 Up to 1.0 X 10 3 , 0.45 X 10 3 Up to 1.0 X 10 3 , 0.5 X 10 3 Up to 1.0 X 10 3 , 0.4 X 10 3 Up to 0.95 X 10 3 , 0.45 X 10 3 Up to 0.95 X 10 3 , 0.5 X 10 3 Up to 0.95 X 10 3 , 0.4 X 10 3 Up to 0.9 X 10 3 , 0.45 X 10 3 Up to 0.9 X 10 3 , or 0.5 X 10 3 Up to 0.9 X 10 3 It is characterized by being.
[0048] Meanwhile, the above NMR analysis was performed on aerogel powder (aerogel particles) detached from the aerogel composite. At this time, the aerogel powder may be obtained from an aerogel composite manufactured in a rectangular shape (e.g., a size of 60 cm x 12 cm, but not limited thereto) or from a specimen piece obtained by cutting a part thereof.
[0049] The aerogel powder used for analysis in this invention can be prepared through the following process: an aerogel composite measuring 60 cm x 12 cm was placed in a sealed container, and the aerogel powder was induced to detach by repeatedly shaking it up and down. To remove the fibrous substrate incorporated within the detached aerogel powder, the fibrous substrate visible to the naked eye was first removed using tweezers. Subsequently, the aerogel powder was placed in a 100 ml vial, distilled water was added at a weight ratio of approximately 1:130 (powder:distilled water), and the container was shaken vigorously 50 times. This removed the fibrous substrate settled at the bottom of the vial and any aggregated clumps formed by the clumping of the fibrous substrate and the aerogel powder, thereby carefully collecting only the aerogel powder floating on the upper layer of the distilled water. At this stage, for sufficient analysis, at least 150 mg of the final obtained aerogel powder sample is required.
[0050] In addition, in the present invention, even when the aerogel composite is heat-treated at a high temperature, the ratio of T1 / T2 to the aerogel particles after heat treatment maintains a level equivalent to the ratio of T1 / T2 to the aerogel particles before heat treatment.
[0051] Specifically, after heat-treating the aerogel particles detached from the aerogel composite at a temperature of 200 ℃ (±5 ℃) for 1 hour, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) in NMR analysis using water solvent for the aerogel particles is 0.4 X 10⁻⁶ 3 Up to 1.0 X 103 , 0.45 X 10 3 Up to 1.0 X 10 3 , 0.5 X 10 3 Up to 1.0 X 10 3 , 0.55 X 10 3 Up to 1.0 X 10 3 , 0.6 X 10 3 Up to 1.0 X 10 3 , 0.4 X 10 3 Up to 0.95 X 10 3 , 0.45 X 10 3 Up to 0.95 X 10 3 , 0.5 X 10 3 Up to 0.95 X 10 3 , 0.55 X 10 3 Up to 0.95 X 10 3 , 0.6 X 10 3 Up to 0.95 X 10 3 , 0.4 X 10 3 Up to 0.9 X 10 3 , 0.45 X 10 3 Up to 0.9 X 10 3 , 0.5 X 10 3 Up to 0.9 X 10 3 , 0.55 X 10 3 Up to 0.9 X 10 3 , 0.6 X 10 3 Up to 0.9 X 10 3 , 0.4 X 10 3 Up to 0.85 X 10 3 , 0.45 X 10 3 Up to 0.85 X 10 3 , 0.5 X 10 3 Up to 0.85 X 10 3 , 0.55 X 10 3 Up to 0.85 X 10 3 , 0.6 X 10 3 Up to 0.85 X 10 3 , 0.4 X 10 3 Up to 0.8 X 10 3 , 0.45 X 10 3Up to 0.8 X 10 3 , 0.5 X 10 3 Up to 0.8 X 10 3 , 0.55 X 10 3 Up to 0.8 X 10 3 , or 0.6 X 10 3 Up to 0.8 X 10 3 It could be.
[0052] In addition, even if the aerogel particles detached from the aerogel composite are heat-treated at a temperature of 200°C for 1 hour, the ratio of T1 / T2 to the aerogel particles may be 0.8 to 1.2 times, 0.85 to 1.2 times, 0.8 to 1.15 times, 0.85 to 1.15 times, 0.8 to 1.1 times, or 0.85 to 1.1 times compared to the ratio of T1 / T2 to the aerogel particles before heat treatment.
[0053] The temperature (or temperature range) described in this specification in relation to heat treatment, etc. accommodates an error range of approximately ±5 ℃.
[0054] The aerogel composite according to the present invention contains pores having a small diameter in a limited proportion, has excellent pore strength, and sufficient hydrophobization occurs not only on the surface of the aerogel composite but also inside the aerogel matrix, particularly inside the pores, so that the degree of pore shrinkage is very low even when heated at high temperatures, and accordingly, can maintain high thermal insulation even when exposed to high-temperature environments.
[0055] In the case where the pore diameter of the aerogel is 20 nm or less, there is a disadvantage that the surface modification must be performed for a long time with a high concentration of hydrophobic modifier in order for the hydrophobic agent to sufficiently diffuse into the pores and achieve sufficient hydrophobization during surface modification due to the small pore size. Accordingly, in the present invention, pores with a pore diameter of 5 to 20 nm are included in a limited proportion within the aerogel.
[0056] The above aerogel may contain pores with a pore diameter of 5 to 20 nm in an amount of 25% or less of the pore volume of the skeletal structure, or 10% or more and 25% or less, but is not limited thereto.
[0057] In the above aerogel composite, the moisture impregnation rate (weight%) represented by Formula 1 below may be 4 weight% or less.
[0058] [Equation 1]
[0059] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100
[0060] In the above Equation 1, the moisture impregnation rate can be calculated by floating a specimen of an aerogel composite measuring 100 mm x 100 mm on distilled water at 21 ± 2 ℃, placing a 6.4 mm mesh screen over the specimen and sinking it to 127 mm below the water surface for impregnation, removing the mesh screen after 15 minutes, and when the specimen floats to the surface, clamping the specimen and suspending it vertically for 60 ± 5 seconds, then measuring the weight before and after impregnation to determine the weight increase rate. Here, a lower moisture impregnation rate indicates a higher degree of hydrophobicity of the aerogel composite.
[0061] In the present invention, surface water repellency and cross-sectional water repellency, used to evaluate the hydrophobicity on the surface and the hydrophobicity inside the aerogel composite, respectively, can both be measured using Equation 1 above, and can be measured by varying the specimen used. Specifically, in the present invention, when measuring the moisture impregnation rate, the moisture impregnation rate measured using a relatively large aerogel composite specimen of 100 mm x 100 mm, which is similar in size to commercially used aerogel composites, is defined as the water repellency on the surface of the aerogel composite. A low surface moisture impregnation rate implies a high degree of hydrophobicity on the surface of the aerogel composite. The surface water repellency of the aerogel composite calculated through Equation 1 above may be 4 weight% or less, or 3.5 weight% or less.
[0062] In addition, when measuring the moisture impregnation rate, the moisture impregnation rate measured using an aerogel composite specimen cut into relatively small sizes, for example, 10 mm x 10 mm, is defined as the water repellency at the cross-section of the aerogel composite. A low cross-sectional moisture impregnation rate implies that the degree of hydrophobicity is high not only on the surface of the aerogel composite but also within it. The cross-sectional water repellency of the aerogel composite calculated through Equation 1 above may be 4 weight% or less, 3 weight% or less, or 2 weight% or less.
[0063] In addition, the aerogel composite may have high hydrophobicity even when heated at a high temperature of 200°C. After heating the aerogel composite at 200°C for 1 hour, the surface water repellency measured according to Formula 1 may be 10% by weight or less, or 5% by weight or less.
[0064] In addition, the aerogel composite may have high hydrophobicity even when heated at a high temperature of 200°C. The cross-sectional water repellency measured according to Formula 1 after heating the aerogel composite at 200°C for 1 hour may be 10% by weight or less, or 5% by weight or less.
[0065] In addition, the aerogel composite may have a water vapor absorption rate of 2.5 weight% or less, as indicated by Formula 2 below. Here, the water vapor absorption rate is expressed in weight% as the amount of water absorbed by the aerogel composite or remaining in the aerogel composite after the aerogel composite is exposed to water vapor under specific measurement conditions. In the present invention, the water vapor absorption rate may be measured by a known method of ASTM C1104.
[0066] [Equation 2]
[0067] Water vapor absorption rate (weight%) = {(Weight of specimen after experiment - Weight of specimen before experiment) / (Weight of specimen before experiment)} X 100
[0068] In addition, the above-mentioned aerogel composite may have a thermal conductivity of 30.0 mW / mK or less, 25.0 mW / mK or less, or 20.0 mW / mK or less at room temperature (23±2 ℃), and within this range, the thermal insulation of the aerogel composite can be maximized.
[0069] The above aerogel composite may have a high temperature (150 ℃) thermal conductivity of 35.0 mW / mK or less, 30.0 mW / mK or less, or 25.0 mW / mK or less, and within this range, the thermal insulation of the aerogel composite can be maximized.
[0070] The above aerogel composite may have excellent mechanical strength, with a compressive strength at 10% strain of 20 kPa to 80 kPa, 20 kPa to 70 kPa, 30 kPa to 80 kPa, 30 kPa to 70 kPa, 35 kPa to 80 kPa, or 35 kPa to 70 kPa. Here, the compressive strength may be measured by preparing a specimen according to ASTM C165.
[0071] The above aerogel composite has a tensile strength of 30 N / cm 2 up to 60 N / cm 2 , 40 N / cm 2 Up to 55 N / cm 2 , or 45 N / cm 2 Up to 55 N / cm 2 As such, it may have excellent flexibility. Here, the tensile strength may be measured by manufacturing a specimen according to ASTM D638 standards.
[0072] The density of the above aerogel composite is 0.05 to 0.50 g / cm³ 3 , 0.05 to 0.35 g / cm² 3 , 0.05 to 0.30 g / cm² 3 , 0.10 to 0.35 g / cm² 3 , 0.10 to 0.30 g / cm² 3 , 0.15 to 0.35 g / cm² 3 1 or 0.15 to 0.30 g / cm² 3 It may be, but is not limited to this.
[0073] In the present invention, the aerogel composite may be formed by the following steps: a step of preparing a silica sol; a step of gelling after impregnating a fiber substrate with the silica sol; a step of aging; a step of surface modification; and a step of drying. Each step is described below. However, the specific manufacturing processes or examples described herein are not intended to limit any specific type of aerogel composite or its manufacturing method. The present specification may include any aerogel composite formed by any associated manufacturing method known to a person skilled in the art.
[0074] Silica sol preparation steps
[0075] In the present invention, a silica sol can be prepared by mixing a silica precursor composition and a catalyst composition.
[0076] The above silica precursor composition may include water and / or a polar organic solvent in the silica precursor.
[0077] The above silica precursor can be any precursor that can be used to form a silica aerogel without limitation, and may be, for example, a silicon-containing alkoxide-based compound. Specifically, tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetrasecondary butyl orthosilicate, tetra tertiary butyl orthosilicate, tetrahexyl orthosilicate, and tetracyclohexyl orthosilicate. It may be a tetraalkyl silicate such as tetradodecyl orthosilicate, or tetradodecyl orthosilicate. More specifically among these, in the case of the present invention, the silica precursor may be tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), or a mixture thereof.
[0078] In addition, the silica precursor may be a water glass solution. Here, the water glass solution may refer to a diluted solution obtained by adding distilled water to water glass and mixing it, and the water glass may be sodium silicate (Na2SiO3), which is an alkali silicate obtained by melting silicon dioxide (SiO2) and an alkali.
[0079] In addition, the silica precursor may include pre-hydrolyzed TEOS (HTEOS). HTEOS is an ethyl silicate oligomer material with a broad molecular weight distribution, and since it can control physical properties such as gelation time when synthesized from TEOS monomers in the form of an oligomer, it can be easily applied according to the user's reaction conditions. Furthermore, it has the advantage of producing reproducible physical properties of the final product. The HTEOS may generally be synthesized by a condensation reaction of TEOS that has undergone a partial hydration step under acidic conditions. That is, the HTEOS may be in the form of an oligomer prepared by condensing TEOS, and the oligomer may be partially hydrated.
[0080] The above silica precursor composition can impart elasticity to the aerogel structure and increase pore strength by further including a silicate containing a hydrophobic group, and can also induce hydrophobicity within the aerogel matrix. The silicate containing the hydrophobic group is not limited in type as long as it is an alkyl silane compound containing a silane functional group capable of reacting with an alkyl group that induces hydrophobicity and a -Si-O- functional group of the wet gel, but specific examples include one or more selected from the group consisting of methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), trimethylsilanol (TMS), methyltrimethoxysilane (MTMS), dimethyldiethoxysilane (DMDEOS), ethyltriethoxysilane (ETES), and phenyltriethoxysilane (PTES), but is not limited thereto.
[0081] When the silica precursor composition above includes a silicate containing the hydrophobic group, it may be included with the tetraalkyl silicate above in a molar ratio of 2:98 to 98:2 (molar ratio of silicate containing the hydrophobic group : tetraalkyl silicate). Within this range, the strength and thermal insulation performance of the aerogel can be secured with high efficiency, while preventing the structural collapse and thus preventing a decrease in thermal insulation performance even when subjected to a high-temperature environment.
[0082] The silica concentration of the above silica precursor composition is 10 kg / m³ 3 up to 100 kg / m² 3 , 20 kg / m 3 up to 80 kg / m² 3 , 30 kg / m 3 Up to 70 kg / m² 3 , 30 kg / m 3 up to 60 kg / m² 3 , or 35 kg / m² 3 Up to 45 kg / m 3 It may be, but is not limited thereto. The above silica concentration is the concentration of silica contained in the silica precursor relative to the silica precursor composition, and can be appropriately adjusted by varying the content of the silica precursor, organic solvent, and water.
[0083] The above silica precursor may be used in an amount such that the silica content contained in the silica sol is 0.1% by weight to 30% by weight, but is not limited thereto. If the silica content satisfies the above range, the mechanical properties of the aerogel composite, particularly flexibility, can be secured at an excellent level while also having an improved thermal insulation effect.
[0084] The above polar organic solvent may include alcohols, specifically examples such as monohydric alcohols like methanol, ethanol, isopropanol, or butanol; polyhydric alcohols like glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, or sorbitol; or combinations thereof, but other solvents known to those skilled in the art may also be used without limitation. Among these, the polar organic solvent may be a monohydric alcohol having 1 to 6 carbon atoms, such as methanol, ethanol, isopropanol, or butanol, such as ethanol, when considering miscibility with water and aerogel.
[0085] The above polar organic solvent can be used in an appropriate amount by a person skilled in the art, taking into account the degree of hydrophobicity in the final aerogel composite while promoting the surface modification reaction.
[0086] When preparing the above-described silica precursor composition, the silica precursor and the organic solvent may be mixed in a weight ratio of 1:0.1 to 5 or 1:0.5 to 3, but are not limited thereto. However, if the silica precursor composition contains a silicate containing hydrophobic groups, the mixture of the silicate containing hydrophobic groups and the tetraalkyl silicate and the organic solvent may be mixed in the above weight ratio.
[0087] In addition, the silica precursor composition may be prepared by mixing the silica precursor and water in a molar ratio of 1:0.5 to 10, 1:1 to 8, or 1:3 to 6, but is not limited thereto. However, if the silica precursor composition contains a silicate containing a hydrophobic group, a mixture of the silicate containing the hydrophobic group and the tetraalkyl silicate and water may be mixed in the above molar ratio.
[0088] The above silica precursor composition may further include an acid catalyst, specifically, when an alkoxysilane compound other than a hydrolysate is used as a precursor, the acid catalyst may further include an acid catalyst. In this case, any acid catalyst that lowers the pH to 3 or lower can be used without limitation, and examples include hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, oxalic acid, or acetic acid. In this case, the acid catalyst may be added in an amount that lowers the pH of the sol to 3 or lower, or it may be added in the form of an aqueous solution dissolved in an aqueous solvent.
[0089] The above catalyst composition may include an inorganic base such as sodium hydroxide or potassium hydroxide as a base catalyst; or an organic base such as ammonium hydroxide. Specific examples include sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia (NH3), ammonium hydroxide (NH4OH; ammonia solution), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, N-methyl diethanolamine, dimethylaminoethanol, diethylaminoethanol, nitrilotriethanol, It may be 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine, dibutanolamine, pyridine, or a combination thereof, but is not limited thereto.
[0090] The above base catalyst may be included in an amount such that the pH of the sol becomes 5 to 9. If the pH of the sol falls outside this range, gelation may not be easy or the gelation rate may become excessively slow, potentially leading to reduced processability. Additionally, since the base may precipitate when added in a solid state, it may be added in a solution diluted by an aqueous solvent or the aforementioned organic solvent. In this case, the dilution ratio of the base catalyst and the organic solvent, specifically the alcohol, may be 1:4 to 1:100 by volume, but is not limited thereto.
[0091] To prepare the silica sol, the silica precursor composition and the catalyst composition may be mixed in a volume ratio of 1:0.01 to 10.0, 1:0.01 to 5.0, or 1:0.01 to 2.0, but are not limited thereto.
[0092] If necessary, additional additives may be added to the silica sol. In this case, any known additives that can be added when manufacturing an aerogel may be used, and for example, additives such as opacifiers and flame retardants may be used.
[0093] The above additive may be added in an amount of 0.1% to 10% by weight, 0.1% to 7% by weight, 0.5% to 7% by weight, or 0.5% to 5% by weight with respect to the silica content of the aerogel, but is not limited thereto.
[0094] Gelation step of silica sol
[0095] In the present invention, silica sol can be impregnated into a substrate and then gelled.
[0096] The above impregnation process is a process that allows the catalytic silica sol to penetrate into the internal pores of the substrate. It can be performed by introducing the catalytic silica sol and the substrate into a reaction vessel, or by spraying the catalytic silica sol onto the substrate moving on a conveyor belt according to a roll-to-roll process. At this time, to improve the bonding between the substrate and the silica sol, the substrate can be lightly pressed to ensure sufficient impregnation. Subsequently, the material can be pressed to a certain thickness under a constant pressure to remove excess silica sol, thereby reducing the drying time.
[0097] The temperature of the silica sol in the reaction vessel may be 1 to 40 ℃, 20 to 40 ℃, 25 to 40 ℃, 30 to 40 ℃, or 35 to 45 ℃. When the temperature of the silica sol in the reaction vessel satisfies the above range, the aforementioned viscosity range of the catalyzed sol can be achieved more easily, and the desired level of viscosity range can be satisfied even with a relatively short residence time.
[0098] The above-mentioned catalytic silica sol can be impregnated into a substrate in a volume ratio of 0.1 to 10:1 (catalytic silica sol:substrate), 0.1 to 1:1, 0.3 to 1:1, 0.5 to 1:1, or 0.6 to 1:1, but is not limited thereto.
[0099] The density ratio of the fiber substrate and the aerogel in the aerogel composite can be controlled by adjusting the ratio of the silica precursor composition, the organic solvent, and water during the preparation of the silica sol, and by adjusting the volume ratio between the silica sol and the substrate during the impregnation step. The strength of the aerogel composite can be increased by making the density ratio of the fiber substrate and the aerogel 1:0.6 to 1.
[0100] The silica sol impregnated in the substrate can be gelled simultaneously with the impregnation process of the silica sol or sequentially after the impregnation process.
[0101] The substrate impregnated with the above-mentioned catalystd sol can be gelled on a moving element such as a conveyor belt.
[0102] The above "gelation" may refer to a sol-gel reaction, and the above "sol-gel reaction" may refer to forming a network structure from a silicon unit precursor material. Here, the network structure may refer to a planar net-like structure in which a specific polygon with one or more types of atomic arrangements is connected, or a structure that forms a three-dimensional skeletal structure by sharing vertices, edges, faces, etc. of a specific polyhedron.
[0103] The above gelation can be performed under an atmosphere temperature of 20 to 40 ℃, 20 to 30 ℃, 25 to 40 ℃, 30 to 40 ℃, or 35 to 40 ℃, and for example, performing it under an atmosphere temperature of 30 to 40 ℃ or 35 to 40 ℃ can increase the strength of the pores in the aerogel composite, but is not limited thereto.
[0104] The above gelation may be performed for 1 to 120 minutes, 1 to 100 minutes, 1 to 60 minutes, 5 to 60 minutes, 5 to 40 minutes, 10 to 40 minutes, 10 to 30 minutes, or 10 to 20 minutes, but can be appropriately controlled by considering the gelation temperature, the amount of silica sol, etc.
[0105] Aging stage of the gelled wet gel complex
[0106] In the present invention, if necessary, an aging step may be further included to allow the wet gel composite obtained by gelation as described above to be left at an appropriate temperature so that chemical changes are completely completed. In the aging step, the network structure formed by gelation can be formed more firmly, thereby improving the mechanical stability of the aerogel composite.
[0107] The above aging step can be performed by leaving the gelled wet gel complex as is at an appropriate temperature, or by adding a cross-linking promoting compound.
[0108] During the above aging step, in the presence of the above wet gel complex, a solution of a base catalyst such as sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), triethylamine, or pyridine diluted in an organic solvent to a concentration of 1 to 10% may be added. In this case, Si-O-Si bonds within the aerogel are induced to the maximum extent, making the network structure of the silica gel more robust and facilitating the maintenance of the pore structure during the subsequent drying process. At this time, the organic solvent may be the aforementioned alcohol, and specifically, may include ethanol.
[0109] In addition, during the aging step, a mixed solution of an alkoxysilane compound and an alcohol can be added to provide not only unreacted sol but also an additional sol precursor source, thereby inducing additional gelation in the silica gel network structure and further strengthening the gel structure. At this time, the alkoxysilane compound may be included in an amount of 0.5 to 9.5 parts by weight, 1.0 to 9.5 parts by weight, or 1.5 to 9.5 parts by weight relative to 100 parts by weight of the total aging solution.
[0110] The above alkoxysilane compounds are tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetrasecondary butyl orthosilicate, tetratertiary butyl orthosilicate, tetrahexyl orthosilicate, and tetracyclohexyl It may include one or more selected from the group consisting of tetracyclohexyl orthosilicate, tetradodecyl orthosilicate, methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), trimethylsilanol (TMS), trimethylchlorosilane (TMCS), ethyltriethoxysilane (ETES), dimethyldiethoxysilane (DMDEOS), and phenyltriethoxysilane.
[0111] In addition, the above alcohol may specifically be a monohydric alcohol such as methanol, ethanol, isopropanol, or butanol; or a polyhydric alcohol such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, or sorbitol, and may be, for example, a monohydric alcohol having 1 to 6 carbon atoms such as methanol, ethanol, isopropanol, or butanol, such as ethanol, but is not limited thereto.
[0112] The above aging step can be performed by leaving the product at a temperature of 30°C to 80°C, 40°C to 80°C, or 50°C to 80°C for 0.1 to 20 hours, 0.5 to 15 hours, 0.5 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours to strengthen the pore structure, and within this range, it is possible to prevent a decrease in productivity while preventing the loss of solvent due to evaporation, thereby preventing an increase in production costs.
[0113] In addition, the above aging step may be performed by first aging at 30°C to 80°C for 0.1 to 5 hours to strengthen the pore structure, and then by adding a solution in which the above-mentioned base catalyst is diluted in an organic solvent, and second aging may be performed at 30°C to 80°C for 0.1 to 20 hours, 0.5 to 15 hours, 0.5 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours.
[0114] In addition, the above aging step may be performed first as described above to strengthen the pore structure as well as to hydrophobize the pores, and then a mixed solution of an alkoxysilane compound and an alcohol may be added to perform a second aging step at 30°C to 80°C for 0.1 to 20 hours, 0.5 to 15 hours, 0.5 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours.
[0115] The above aging step may be performed in a separate reaction vessel after recovering the gelled wet gel complex, or it may be performed inside the reaction vessel where the gelling step was performed.
[0116] Surface modification step of aged wet gel complex
[0117] The present invention may further include a surface modification step in which the surface of the wet gel composite obtained by gelation as described above or the aged wet gel composite is hydrophobized in the presence of a surface modifier, if necessary.
[0118] The above surface modifier may be any compound that hydrophobicizes the wet gel surface without limitation, such as a silane compound, a siloxane compound, a silanol compound, a silazane compound, or a combination thereof. Specific examples include silane compounds comprising trimethylchlorosilane (TMCS), dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), vinyltrimethoxysilane, ethyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, tetraethoxysilane, dimethyldichlorosilane, or 3-aminopropyltriethoxysilane; and siloxane compounds comprising polydimethylsiloxane, polydiethylsiloxane, or octamethylcyclotetrasiloxane. Silanol-based compounds including trimethylsilanol, triethylsilanol, triphenylsilanol, and t-butyldimethylsilanol, etc.; silazane-based compounds including 1,2-diethyldisilazane, 1,1,2,2-tetramethyldisilazane, 1,1,3,3-tetramethyldisilazane, 1,1,1,2,2,2-hexamethyldisilazane (HMDS), 1,1,2,2-tetraethyldisilazane, or 1,2-diisopropyldisilazane, etc.; or a combination thereof, but not limited thereto.
[0119] The above surface modifier may be used as a solution diluted in an organic solvent. Here, the organic solvent may be an alcohol (organic solvent), and the surface modifier may be diluted to 1 to 15 volume% based on the total volume of the diluted solution.
[0120] In addition, the above surface modifier may be added in an amount of 0.01 to 90 volume% with respect to the wet gel composite for a sufficient surface modification effect, but is not limited thereto.
[0121] The surface modification step may be performed for 1 to 24 hours or 6 to 12 hours at a temperature of 50 to 90 ℃ or 50 to 80 ℃, but is not limited thereto.
[0122] drying stage
[0123] The present invention may include a drying step of drying a surface-modified wet gel composite to obtain an aerogel composite.
[0124] The above drying is performed as a process that removes only the solvent while maintaining the pore structure of the aged gel, and can be performed, for example, by supercritical drying or atmospheric pressure drying.
[0125] The above supercritical drying process is performed using supercritical carbon dioxide. For example, a matured wet gel complex is placed into a supercritical drying reactor, and then liquid CO2 is filled and a solvent exchange process is performed to replace the alcohol solvent inside the wet gel with CO2. Afterward, the temperature is raised to 40 to 70 ℃ at a constant heating rate, e.g., 0.1 ℃ / min to 1 ℃ / min. Subsequently, a pressure greater than the pressure at which carbon dioxide reaches a supercritical state, e.g. 100 bar to 150 bar, is maintained to maintain the carbon dioxide in a supercritical state for a certain period of time, specifically 20 minutes to 1 hour. Generally, carbon dioxide reaches a supercritical state at a temperature of 31 ℃ and a pressure of 73.8 bar. An aerogel composite can be manufactured by maintaining the carbon dioxide at a constant temperature and constant pressure for 2 to 12 hours, more specifically 2 to 6 hours, and then gradually removing the pressure to complete the supercritical drying process, but is not limited thereto.
[0126] In addition, the above atmospheric pressure drying process may be performed for 30 minutes to 4 hours according to conventional methods such as hot air drying or IR drying at a temperature of 70 to 200 ℃ and atmospheric pressure (1±0.3 atm), but is not limited thereto.
[0127] In addition to the above-described process, the present invention includes the acidification of a basic metal oxide precursor (e.g., sodium silicate) in water to produce a hydrogel. Salt byproducts can be removed from the silicate precursor by ion exchange and / or by subsequent washing of the formed gel with water. Removal of water from the pores of the gel can be carried out through exchange with a polar organic solvent, such as ethanol, methanol, or acetone. Subsequently, the liquid phase in the gel is at least partially extracted using innovative processing and extraction techniques.
[0128] In addition to the above-described process, the present invention includes reducing damaging capillary forces at the solvent / pore interface by chemically modifying the matrix material in a wet gel state through the conversion of surface hydroxyl groups to hydrophobic trimethylsilyl ether, thereby enabling liquid phase extraction from the gel material at temperatures and pressures below the critical point of the solvent.
[0129] In addition to the above-described process, the liquid (solvent) within the gel material may be frozen at a lower temperature and subsequently subjected to a sublimation process to remove the solvent from the gel material. Such removal or drying of the solvent from the gel material is understood to be within the scope of the present disclosure. Such removal largely preserves the gel structure, thereby producing an aerogel with unique properties.
[0130] The aerogel composite provided in the present invention can be usefully used as an insulating material, thermal insulation material, or non-combustible material for various industrial equipment piping or industrial furnaces, as well as for plant facilities for thermal insulation, thermal insulation, etc., and for aircraft, ships, automobiles, electronic devices, batteries, etc.
[0132] According to another embodiment of the present invention, the invention relates to an aerogel comprising a plurality of open pores and a plurality of silica aerogel particles.
[0133] The above aerogel may be detached from the aerogel composite provided in the present invention.
[0134] As a result of performing NMR analysis on the above aerogel particles using water (H2O) as the saturation fluid, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) was 0.4 X 10 3 Up to 1.0 X 10 3 , 0.45 X 10 3 Up to 1.0 X 10 3 , 0.5 X 10 3 Up to 1.0 X 10 3 , 0.4 X 10 3Up to 0.95 X 10 3 , 0.45 X 10 3 Up to 0.95 X 10 3 , 0.5 X 10 3 Up to 0.95 X 10 3 , 0.4 X 10 3 Up to 0.9 X 10 3 , 0.45 X 10 3 Up to 0.9 X 10 3 , or 0.5 X 10 3 Up to 0.9 X 10 3 It is characterized by being.
[0135] In addition, after heat-treating the aerogel particles at a temperature of 200 ℃ (±5 ℃) for 1 hour, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) in NMR analysis using water solvent for the aerogel particles is 0.4 X 10⁻⁶ 3 Up to 1.0 X 10 3 , 0.45 X 10 3 Up to 1.0 X 10 3 , 0.5 X 10 3 Up to 1.0 X 10 3 , 0.55 X 10 3 Up to 1.0 X 10 3 , 0.6 X 10 3 Up to 1.0 X 10 3 , 0.4 X 10 3 Up to 0.95 X 10 3 , 0.45 X 10 3 Up to 0.95 X 10 3 , 0.5 X 10 3 Up to 0.95 X 10 3 , 0.55 X 10 3 Up to 0.95 X 10 3 , 0.6 X 10 3 Up to 0.95 X 10 3 , 0.4 X 10 3 Up to 0.9 X 10 3 , 0.45 X 10 3 Up to 0.9 X 10 3 , 0.5 X 103 Up to 0.9 X 10 3 , 0.55 X 10 3 Up to 0.9 X 10 3 , 0.6 X 10 3 Up to 0.9 X 10 3 , 0.4 X 10 3 Up to 0.85 X 10 3 , 0.45 X 10 3 Up to 0.85 X 10 3 , 0.5 X 10 3 Up to 0.85 X 10 3 , 0.55 X 10 3 Up to 0.85 X 10 3 , 0.6 X 10 3 Up to 0.85 X 10 3 , 0.4 X 10 3 Up to 0.8 X 10 3 , 0.45 X 10 3 Up to 0.8 X 10 3 , 0.5 X 10 3 Up to 0.8 X 10 3 , 0.55 X 10 3 Up to 0.8 X 10 3 , or 0.6 X 10 3 Up to 0.8 X 10 3 It could be.
[0136] In addition, even if the aerogel particles are heat-treated at a temperature of 200°C for 1 hour, the ratio of T1 / T2 to the aerogel particles may be 0.8 to 1.2 times, 0.85 to 1.2 times, 0.8 to 1.15 times, 0.85 to 1.15 times, 0.8 to 1.1 times, or 0.85 to 1.1 times compared to the ratio of T1 / T2 to the aerogel particles before heat treatment.
[0137] The above aerogel may contain pores with a pore diameter of 5 to 20 nm in an amount of 25% or less of the pore volume of the skeletal structure, or 10% or more and 25% or less, but is not limited thereto.
[0139] According to another embodiment of the present invention, the invention relates to an insulating member comprising an aerogel composite provided in the present invention.
[0140] The above-described insulating member may include the aerogel composite described above and a supporting member located on at least one of the upper and lower surfaces of the aerogel composite.
[0141] Examples of the above-mentioned support members include film-type support members, sheet-type support members, thin-film support members, porous support members, etc.
[0142] The above film-like support member is formed by molding a polymer raw material into a thin film, and examples include organic films such as PET and polyimide, glass films, etc. (metal deposition films are also included).
[0143] The above sheet-like support member is formed from organic, inorganic, or metal fiber-like raw materials, and examples include paper, non-woven fabric (including glass mats), organic fiber fabric, glass cloth, etc.
[0144] The above-mentioned thin film support member is formed by molding a metal raw material into a thin film, and examples include aluminum foil or copper foil.
[0145] The above porous support member has a porous structure made of organic, inorganic, or metal raw materials, and may include porous organic materials (e.g., polyurethane foam), porous inorganic materials (e.g., zeolite sheets), or porous metal materials (e.g., porous metal sheets, porous aluminum sheets).
[0146] The thickness of the above-mentioned support member is not particularly limited and may be, for example, 0.1 to 100 μm, or 1 to 50 μm.
[0147] The above-mentioned insulating member can also be applied for use as an insulating material, thermal insulation material, or non-combustible material in the construction, aviation, automotive, battery, home appliance, semiconductor, and industrial equipment sectors.
[0149] According to another embodiment of the present invention, the invention relates to a battery module or battery pack comprising an aerogel composite according to the present invention.
[0150] The battery module may include a module case having an internal space and one or more battery cells existing within the internal space. The number of battery cells accommodated in the module case is not limited in any specific way and can be adjusted according to the application of the battery module. The battery cells accommodated in the module case may be electrically connected to one another. The type of battery cell accommodated in the module case is not limited, but, for example, the battery module may include cylindrical, prismatic, or pouch-type case battery cells.
[0151] The battery module may include an aerogel composite according to the present disclosure within the module case of the battery module. The aerogel composite may be positioned between battery cells accommodated within the module case. The aerogel composite may be positioned between the module case and a plurality of battery cells, i.e., around the module case. The aerogel composite positioned within the module case may act as an insulator to reduce heat propagation within the battery module and improve the safety of the battery module.
[0152] The battery pack may include one or more of the battery modules. In the battery pack, the battery modules may be electrically connected to each other. The battery pack may include an aerogel composite according to the present disclosure. For example, the aerogel composite may be located between the battery modules of the battery pack. The aerogel composite may also at least partially surround a plurality of battery modules within the battery pack. The aerogel composite may act as an insulating material within the battery pack to reduce heat propagation and improve the safety of the battery pack.
[0154] The present invention will be explained in detail below through the following examples. However, the following examples are merely illustrative of the present invention, and the scope of the present invention is not limited by the following examples.
[0156] Examples
[0158] [Example 1] Preparation of an Aerogel Composite
[0159] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a 1:1 molar ratio. A silica sol was prepared by mixing the silica precursor composition with water in a 1:5 molar ratio and adding ethanol in a 1:2 weight ratio with the silica precursor composition. Hydrochloric acid was added to ensure the pH of the silica sol was 3 or lower to promote hydrolysis. A catalyzed silica sol was prepared by adding a base catalyst solution (10 wt% NaOH aqueous solution) in a 99:1 volume ratio with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 3 mm) as a substrate, ensuring that the catalyzed silica sol impregnated the fiber mat in a 1:1 volume ratio (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed. At this time, the ambient temperature on the conveyor belt was maintained at 25°C. A 1.7 wt% tetraethyl orthosilicate (TEOS) solution (solvent: ethanol) was prepared as an aging solution and added to the manufactured wet gel composite at 109% of the volume of the wet gel composite, and aging was carried out in a 75°C oven for 2 hours. A 10 wt% solution of trimethylethoxysilane (TMES) diluted in ethanol was added to the wet gel composite at 90 wt% of the volume of the wet gel composite as a surface modifier, and surface modification was performed at a temperature of 75°C for 12 hours. The silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Subsequently, the temperature inside the extractor was raised to 70°C over a period of 1 hour and 20 minutes. When 70°C and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the process of stopping CO2 injection and maintaining the state for 20 minutes was repeated 4 times. Ethanol was recovered through the bottom of the extractor during CO2 injection and discharge.Subsequently, a hydrophobic silica aerogel composite was prepared by venting CO2 over a period of 2 hours.
[0161] [Example 2] Preparation of an Aerogel Composite
[0162] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a molar ratio of 7:3. A silica sol was prepared by mixing the silica precursor composition with water in a molar ratio of 1:5 and adding ethanol in a weight ratio of 1:2 with the silica precursor composition. Hydrochloric acid was added to ensure the pH of the silica sol was 3 or lower to promote hydrolysis. A catalyzed silica sol was prepared by adding a base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 3 mm) as a substrate, ensuring that the catalyzed silica sol was impregnated into the fiber mats in a volume ratio of 1:1 (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this time, the ambient temperature on the conveyor belt was maintained at 35 ℃. After gelation was complete, the mixture was stabilized at room temperature (25 ℃) for 10 minutes, followed by primary aging in a 70 ℃ oven for 30 minutes. Subsequently, a 3.4 wt% tetraethyl orthosilicate (TEOS) solution (solvent: ethanol) was prepared and added to the gelled wet gel composite at 109% of the wet gel composite volume, followed by secondary aging in a 75 ℃ oven for 2 hours. A 10 vol% solution of trimethylethoxysilane (TMES) diluted in ethanol was added to the wet gel composite at 90 vol% of the wet gel composite volume as a surface modifier, and surface modification was performed at a temperature of 75 ℃. 8 hours The process was carried out for a period of time. A silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Subsequently, the temperature inside the extractor was raised to 70 °C over a period of 1 hour and 20 minutes. Upon reaching 70 °C and 150 bar, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the process of stopping CO2 injection and maintaining the state for 20 minutes was repeated 4 times. Ethanol was recovered through the bottom of the extractor during CO2 injection and discharge. Afterward, CO2 was vented over a period of 2 hours to prepare a hydrophobic silica aerogel composite.
[0164] [Example 3] Preparation of an Aerogel Composite
[0165] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a molar ratio of 7:3. A silica sol was prepared by mixing the silica precursor composition with water in a molar ratio of 1:5 and adding ethanol in a weight ratio of 1:2 with the silica precursor composition. Hydrochloric acid was added to ensure the pH of the silica sol was 3 or lower to promote hydrolysis. A catalyzed silica sol was prepared by adding a base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 3 mm) as a substrate, ensuring that the catalyzed silica sol was impregnated into the fiber mats in a volume ratio of 1:1 (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed. At this time, the ambient temperature on the conveyor belt was maintained at 25 ℃. After gelation was complete, the mixture was stabilized at room temperature (25 ℃) for 10 minutes, followed by primary aging in a 70 ℃ oven for 30 minutes. Subsequently, a mixture of ethanol and ammonia water (volume ratio of 98:2) was prepared and added to the gelled wet gel composite in an amount 1.6 times the volume of the silica sol, and secondary aging was carried out in a 70 ℃ oven for 1 hour. A solution of trimethylethoxysilane (TMES) diluted in ethanol (10 vol%) was added to the wet gel composite at 90 vol% based on the volume of the wet gel composite as a surface modifier, and surface modification was performed at a temperature of 75 ℃ for 10 hours. The silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Afterwards, the temperature inside the extractor was raised to 70 ℃ over 1 hour and 20 minutes, and when 70 ℃ and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the process of stopping CO2 injection for 20 minutes was repeated 4 times.Ethanol was recovered through the bottom of the extractor during CO2 injection and exhaust. Subsequently, a hydrophobic silica aerogel composite was prepared by venting CO2 over a period of 2 hours.
[0167] [Example 4] Preparation of an Aerogel Composite
[0168] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a molar ratio of 7:3. A silica sol was prepared by mixing the silica precursor composition with water in a molar ratio of 1:5 and adding ethanol in a weight ratio of 1:2 with the silica precursor composition. Hydrochloric acid was added to ensure the pH of the silica sol was 3 or lower to promote hydrolysis. A catalyzed silica sol was prepared by adding a base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 3 mm) as a substrate, ensuring that the catalyzed silica sol was impregnated into the fiber mats in a volume ratio of 1:1 (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed. At this time, the ambient temperature on the conveyor belt was maintained at 35°C. After gelation was complete, the mixture was stabilized at room temperature (25°C) for 10 minutes, followed by primary aging in a 70°C oven for 30 minutes. Subsequently, a solution of 2.9 wt% methyltriethoxysilane (MTES) diluted in ethanol with a moisture content of 10 wt% was prepared and added to the gelled wet gel composite at 109% of the volume of the wet gel composite, followed by secondary aging in a 75°C oven for 2 hours. A solution of trimethylethoxysilane (TMES) diluted in ethanol (10 vol%) was added to the wet gel composite at 90 vol% of the volume of the wet gel composite as a surface modifier, and surface modification was performed at 75°C for 10 hours. The silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Afterwards, the temperature inside the extractor was raised to 70 ℃ over 1 hour and 20 minutes, and when 70 ℃ and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the process of stopping CO2 injection for 20 minutes was repeated 4 times.Ethanol was recovered through the bottom of the extractor during CO2 injection and exhaust. Subsequently, a hydrophobic silica aerogel composite was prepared by venting CO2 over a period of 2 hours.
[0170] [Example 5] Preparation of an Aerogel Composite
[0171] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a molar ratio of 7:3. A silica sol was prepared by mixing the silica precursor composition with water in a molar ratio of 1:5 and adding ethanol in a weight ratio of 1:2 with the silica precursor composition. Hydrochloric acid was added to ensure the pH of the silica sol was 3 or lower to promote hydrolysis. A catalyzed silica sol was prepared by adding a base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 3 mm) as a substrate, ensuring that the catalyzed silica sol was impregnated into the fiber mats in a volume ratio of 1:1 (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed. At this time, the ambient temperature on the conveyor belt was maintained at 25 ℃. After gelation was complete, the mixture was stabilized at room temperature (25 ℃) for 10 minutes, followed by primary aging in a 70 ℃ oven for 30 minutes. Subsequently, a mixture of ethanol and ammonia water (volume ratio of 98:2) was prepared and added to the gelled wet gel composite in an amount 1.6 times the volume of the silica sol, and secondary aging was carried out in a 70 ℃ oven for 1 hour. A solution of trimethylethoxysilane (TMES) diluted in ethanol (10 vol%) was added to the wet gel composite at 90 vol% based on the volume of the wet gel composite as a surface modifier, and surface modification was performed at a temperature of 75 ℃ for 8 hours. The silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Afterwards, the temperature inside the extractor was raised to 70 ℃ over 1 hour and 20 minutes, and when 70 ℃ and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the process of stopping CO2 injection for 20 minutes was repeated 4 times.Ethanol was recovered through the bottom of the extractor during CO2 injection and exhaust. Subsequently, a hydrophobic silica aerogel composite was prepared by venting CO2 over a period of 2 hours.
[0173] [Comparative Example 1] Preparation of an aerogel composite
[0174] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a molar ratio of 9:1. A silica sol was prepared by mixing the silica precursor composition with water in a molar ratio of 1:5 and adding ethanol in a weight ratio of 1:2 with the silica precursor composition. Hydrochloric acid was added to ensure the pH of the silica sol was 3 or lower to promote hydrolysis. A catalyzed silica sol was prepared by adding a base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 3 mm) as a substrate, ensuring that the catalyzed silica sol was impregnated into the fiber mats in a volume ratio of 1:1 (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed. At this time, the ambient temperature on the conveyor belt was maintained at 25 ℃. A silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Subsequently, the temperature inside the extractor was raised to 70 ℃ over 1 hour and 20 minutes. Once 70 ℃ and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the CO2 injection was stopped for 20 minutes. This process was repeated 4 times. Ethanol was recovered through the bottom of the extractor during the CO2 injection and discharge. Afterward, CO2 was vented over a period of 2 hours to produce a hydrophobic silica aerogel composite.
[0176] [Comparative Example 2] Preparation of an aerogel composite
[0177] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and ethanol in a weight ratio of 1:0.5 and adding water in a molar ratio of 1:4 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:0.8 with the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalytic sol into an impregnation tank, the catalytic sol was passed through a fiber (glass fiber mat, 3 mm) as a substrate to infiltrate the fiber, ensuring that the catalytic silica sol impregnated the fiber mat in a volume ratio of 1:1 (catalytic silica sol: fiber). Fibers infiltrated with the catalyzed sol after passing through an impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 25°C. A solution of trimethylethoxysilane (TMES) diluted in ethanol (10 vol%) was added to the wet gel composite as a surface modifier at 90 vol% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 10 hours. The silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Subsequently, the temperature inside the extractor was raised to 70°C over 1 hour and 20 minutes. Upon reaching 70°C and 150 bar, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, followed by stopping the CO2 injection for 20 minutes; this process was repeated four times. Ethanol was recovered through the bottom of the extractor during the CO2 injection and discharge. Subsequently, a hydrophobic silica aerogel composite was prepared by venting CO2 over a period of 2 hours.
[0179] [Comparative Example 3] Preparation of an aerogel composite
[0180] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and ethanol in a weight ratio of 1:0.5 and adding water in a molar ratio of 1:4 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:0.8 with the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalytic sol into an impregnation tank, the catalytic sol was passed through a fiber (glass fiber mat, 3 mm) as a substrate to infiltrate the fiber, ensuring that the catalytic silica sol impregnated the fiber mat in a volume ratio of 1:1 (catalytic silica sol: fiber). Fibers infiltrated with the catalyzed sol after passing through an impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 35°C. A solution of trimethylethoxysilane (TMES) diluted in ethanol (10 vol%) was added to the wet gel composite as a surface modifier at 90 vol% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 4 hours. The silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Subsequently, the temperature inside the extractor was raised to 70°C over 1 hour and 20 minutes. Upon reaching 70°C and 150 bar, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, followed by stopping the CO2 injection for 20 minutes; this process was repeated 4 times. Ethanol was recovered through the bottom of the extractor during the CO2 injection and discharge. Subsequently, a hydrophobic silica aerogel composite was prepared by venting CO2 over a period of 2 hours.
[0182] [Comparative Example 4] Preparation of an aerogel composite
[0183] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and ethanol in a weight ratio of 1:0.5 and adding water in a molar ratio of 1:4 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:0.8 with the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalytic sol into an impregnation tank, the catalytic sol was passed through a fiber (glass fiber mat, 3 mm) as a substrate to infiltrate the fiber, ensuring that the catalytic silica sol impregnated the fiber mat in a volume ratio of 1:1 (catalytic silica sol: fiber). Fibers infiltrated with the catalyzed sol after passing through an impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 35°C. A solution of trimethylethoxysilane (TMES) diluted in ethanol (10 vol%) was added to the wet gel composite as a surface modifier at 90 vol% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 10 hours. The silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Subsequently, the temperature inside the extractor was raised to 70°C over 1 hour and 20 minutes. Upon reaching 70°C and 150 bar, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, followed by stopping the CO2 injection for 20 minutes; this process was repeated four times. Ethanol was recovered through the bottom of the extractor during the CO2 injection and discharge. Subsequently, a hydrophobic silica aerogel composite was prepared by venting CO2 over a period of 2 hours.
[0185] [Comparative Example 5] Preparation of an aerogel composite
[0186] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and ethanol in a weight ratio of 1:0.5 and adding water in a molar ratio of 1:4 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:0.8 with the hydrated TEOS solution. Hydrochloric acid was added to lower the pH of the silica sol to 3 or lower to promote hydrolysis. A catalyzed silica sol was prepared by adding a base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling the impregnation tank with 33.3 L of this catalyzed sol, the catalytic sol was passed through a fiber (glass fiber mat, 3 mm) as a substrate to infiltrate the fiber, ensuring that the catalyzed silica sol was impregnated into the fiber mat at a volume ratio of 1:1 (catalytic silica sol: fiber). The fiber, having passed through the impregnation tank and infiltrated with the catalyzed sol, passed over a conveyor belt at a constant speed and gelled. During this process, the ambient temperature on the conveyor belt was maintained at 25 ℃. To the prepared wet gel composite, a solution of 2.4 wt% ammonia water (NH4OH) diluted in ethanol with a moisture content of 10 wt% was added as an aging solution at 109% based on the volume of the wet gel blanket, and aging was carried out at a temperature of 75 ℃ for 1 hour. A solution of trimethylethoxysilane (TMES) diluted in ethanol (10 vol%) was added to the wet gel composite as a surface modifier at 90 vol% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75 °C for 6 hours. The silica wet gel composite was placed in a 7.2 L supercritical extractor, and CO2 was injected. Subsequently, the temperature inside the extractor was raised to 70 °C over 1 hour and 20 minutes, and upon reaching 70 °C and 150 bar, 0.The process of injecting and exhausting CO2 at a rate of 5 L / min and maintaining a stopped CO2 injection for 20 minutes was repeated 4 times. Ethanol was recovered through the bottom of the extractor during CO2 injection and exhaust. Subsequently, CO2 was vented over a period of 2 hours to produce a hydrophobic silica aerogel composite.
[0188] [Experimental Example 1] Measurement of Distribution by Density and Pore Size
[0189] 1. Density
[0190] For each silica aerogel composite prepared in each example and comparative example, five specimens measuring 10 cm x 10 cm were prepared, and their weights were measured. The thickness of each specimen was measured using a NETZSCH HFM436 instrument. The density was calculated based on the measured weight, thickness, and size, and the average density of the five specimens was determined as the final density. The results are shown in Table 1 below.
[0191] 2. Volume ratio of effective pores with a diameter of 5–20 nm (%)
[0192] For each silica aerogel composite prepared in each example and comparative example, the partial pressure (0.11) was measured using a Micrometrics ASAP 2010 instrument. <p / p0<1)에 따른 질소의 흡 / 탈착량으로 분석하여, 비표면적, 기공 부피 및 기공 직경을 측정하였다. 측정된 기공 부피에서 기공 직경이 5~20 nm의 수치범위를 갖는 기공(유효 기공)의 부피 비율을 산출하여 그 결과를 하기 표 1에 나타내었다.
[0193] division Density (g / cc) Effective pore volume ratio (%) Example 1 0.211 17% Example 2 0.221 20.1% Example 3 0.199 24.5% Example 4 0.218 16.4% Example 5 0.205 14.5% Comparative Example 1 0.215 28.3% Comparative Example 2 0.189 28% Comparative Example 3 0.199 30.1% Comparative Example 4 0.195 28.8% Comparative Example 5 0.211 32.2%
[0195] [Experimental Example 2] NMR Analysis of Aerogel Structure
[0196] 1. Room temperature NMR analysis
[0197] In order to perform NMR analysis on the aerogel particles contained in the aerogel composites obtained in Examples 1 to 5 and Comparative Examples 1 to 5, the aerogel composites of Examples 1 to 5 and Comparative Examples 1 to 5 were first prepared with dimensions of 60 cm x 12 cm. Each aerogel composite was placed in a sealable vinyl container and subjected to repeated shaking up and down to intentionally induce the detachment of the aerogel powder (aerogel particles). The fibrous substrates mixed in the obtained aerogel powder and identifiable to the naked eye were removed with tweezers. Subsequently, to further remove the finely mixed fibrous substrates within the detached powder for more precise analysis, the aerogel powder was placed in a 100 ml vial, distilled water was added so that the weight ratio of powder to distilled water was approximately 1:130, and the vigorously shaken up and down 50 times. Afterward, the fibrous substrates settled at the bottom of the vial were removed, and any lumps formed by the aggregation of the fibrous substrates and the aerogel powder were also removed. Only 150 mg of aerogel powder that had not formed aggregates was carefully obtained and dried in a 105 ℃ condition oven (Samhong Energy Co., Ltd., SH-VDO-08NG) for more than 24 hours. The dried aerogel powder was stored in a constant temperature and humidity chamber (JEIO TECH, TH3-PE) at a temperature of 25 ℃ and a humidity of 40% for more than 5 hours to allow water to adsorb and saturate the aerogel pores. The aerogel powder saturated with water in the pores was transferred to a 5 mm NMR tube, sealed, and NMR experiments were performed. A 600 MHz NMR (Bruker, Avance Neo) and a diffusion probe were used as the NMR instrument. The experimental parameters for measuring the T1 relaxation time were pulse sequence: T1 inversion recovery method, d1=10 seconds, ns=8, and vdlist as shown in Table 2 below.The experimental parameters for measuring T2 relaxation time were pulse sequence: CPMG (Car-Purcell-Meiboom-Gill) method, d1=10 seconds, ns=8, ds=16, d20=0.000150 seconds, and vclist as shown in Table 3 below. The T1 relaxation time and T2 relaxation time for each specimen obtained through this experiment, and their ratio (T1 / T2), are shown in Table 4 below. In Table 4 below, the T1 and T2 relaxation time results are presented as average values after three repeated experiments.
[0198] vdlist 1 2 3 4 5 6 7 8 9 10 11 12 Delay time 0.01 0.04 0.09 0.16 0.25 0.49 1 2 4 9 16 25
[0199] vclist 1 2 3 4 5 6 7 8 9 10 11 12 13 14 Loop count 0 1 2 3 4 5 6 7 8 10 12 14 16 32
[0200] T1(sec) T2(msec) T1 / T2(*10^3) Example 1 1.463 2.8 0.52 Example 2 1.34 2.2 0.61 Example 3 1.482 2.19 0.68 Example 4 1.38 1.7 0.81 Example 5 1.29 1.43 0.90 Comparative Example 1 1.45 1.07 1.36 Comparative Example 2 1.3 0.922 1.41 Comparative Example 3 1.48 1.16 1.28 Comparative Example 4 1.22 0.8 1.53 Comparative Example 5 1.51 1.19 1.27 Bulk H2O 2.83 2.81
[0201] As shown in Table 4 above, the NMR analysis results using water solvent for the aerogel composites of Examples 1 to 5 according to the present invention showed that the T1 / T2 ratio was 0.4 x 10⁻⁶ 3 Up to 1.0 X 10 3 It was possible to confirm that it was.
[0202] 2. High-temperature NMR analysis
[0203] The following experiment was conducted to determine whether shrinkage of the pore structure or changes in the hydrophobicity of the surface or inside the pores of the aerogel composites occur when high-temperature heat treatment similar to atmospheric pressure drying is performed on the aerogel composites obtained in Examples 1 to 5 and Comparative Examples 1 to 5. Specifically, aerogel composites of Examples 1 to 5 and Comparative Examples 1 to 5 were prepared with dimensions of 60 cm x 12 cm, and aerogel powder was obtained from the aerogel composites using the same method as in 1. Room temperature NMR analysis above. After heat-treating the aerogel powder at a temperature of 200 ℃ for 1 hour, the T1 relaxation time and T2 relaxation time for each specimen were measured via NMR analysis, and the ratio (T1 / T2) was calculated and shown in Table 5 below. In addition, the ratio of the T1 / T2 ratio obtained after heat treatment to the ratio of the T1 / T2 ratio obtained before heat treatment (indicated as "after heat treatment / before heat treatment") was calculated, and the results are shown together in Table 5.
[0204] T1 / T2(*10^3) After heat treatment / Before heat treatment Example 1 0.57 1.09 Example 2 0.62 1.02 Example 3 0.64 0.95 Example 4 0.8 0.99 Example 5 0.78 0.86 Comparative Example 1 2.94 0.46 Comparative Example 2 3.22 0.44 Comparative Example 3 2.35 0.54 Comparative Example 4 2.16 0.71 Comparative Example 5 1.70 0.75 Bulk H2O 2.94
[0205] As shown in Table 5 above, after heat-treating the aerogel composites of Examples 1 to 5 according to the present invention at a high temperature of 200 °C, the results of NMR analysis using water solvent showed that the T1 / T2 ratio was also 0.4 X 10⁻⁶ 3 Up to 1.0 X 10 3It was confirmed that the level was [described as]. In addition, the ratio of T1 / T2 after heat treatment to T1 / T2 before heat treatment was approximately 0.8 to 1.2 times, showing a T1 / T2 ratio similar to that before heat treatment even after heat treatment. On the other hand, for the aerogel composites of Comparative Examples 1 to 5, the ratio of T1 / T2 after heat treatment to T1 / T2 before heat treatment was at most 0.75 times and mostly less than 0.70 times, confirming that the T1 / T2 after heat treatment was significantly reduced compared to before heat treatment. Through the above experiments, it was found that the aerogel composite according to the present invention has high pore strength and sufficient hydrophobicity occurs within the pores, so even when exposed to a high-temperature environment, it is possible to prevent the pores from shrinking and deforming or the hydrophobicity on the surface and inside the aerogel composite from significantly decreasing.
[0207] [Experimental Example 3] Evaluation of hydrophobicity of aerogel composite (1)
[0208] 1. Room temperature hydrophobicity evaluation
[0209] The following experiment was performed to evaluate the surface and internal hydrophobicity of the aerogel composite prepared according to the present invention.
[0210] 1-1. Measurement of surface water repellency
[0211] First, specimens measuring 10 cm x 10 cm (thickness approximately 5 mm) were obtained from each of the aerogel composites of Examples 1 to 5 and Comparative Examples 1 to 5, floated on distilled water at a temperature of 21 ± 2 ℃, and then a 6.4 mm mesh screen was lowered 127 mm below the water surface (impregnation). After 15 minutes, the mesh screen was removed, and once the specimen floated to the surface, the specimen was clamped and suspended vertically for 60 ± 5 seconds. Subsequently, the weight of the specimen before and after impregnation was measured and calculated according to Equation 1 below, and expressed as surface water repellency. A lower surface water repellency value indicates superior hydrophobicity of the silica aerogel composite surface. Note that the experimental results for surface water repellency in Table 6 below represent the average value after performing three repeated experiments. The average value was rounded to the second decimal place.
[0212] [Equation 1]
[0213] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100
[0214] 1-2. Measurement of surface water repellency
[0215] Cross-sectional water repellency was measured by cutting a specimen of 10 cm x 10 cm into 1 cm x 1 cm pieces (thickness approximately 3 mm) using the same method as the surface water repellency described above. However, considering the size of the specimens, five specimens were prepared for each example or comparative example, and the same experiment was repeated three times for each specimen to determine the cross-sectional water repellency, with the result expressed as the average value. The average value was rounded to the second decimal place. Here, a lower cross-sectional water repellency value indicates superior internal hydrophobicity of the silica aerogel composite.
[0216] division Surface water repellency (weight%) Surface water repellency (weight%) Example 1 1.86 1.12 Example 2 1.05 0.63 Example 3 2.13 1.08 Example 4 1.13 0.72 Example 5 3.14 1.21 Comparative Example 1 10.13 6.68 Comparative Example 2 5.64 5.52 Comparative Example 3 12.02 8.15 Comparative Example 4 4.71 4.29 Comparative Example 5 8.07 7.85
[0217] As shown in Table 6 above, the surface water repellency of the aerogel composites according to the present invention (Examples 1 to 5) is low at approximately 4 wt% or less, and the cross-sectional water repellency is also very low at 1.5 wt% or less. Through this, it was found that the aerogel composites according to the present invention have high surface and internal hydrophobicity and excellent water repellency. On the other hand, the surface water repellency of the aerogel composites of Comparative Examples 1 to 5 is at a level exceeding 4 wt%, and the cross-sectional water repellency is very low at a minimum of 3.65 wt% and a maximum of 6.24 wt%, and in particular, the hydrophobicity within the aerogel composite is low.
[0218] 2. High-temperature hydrophobicity evaluation
[0219] In order to evaluate whether hydrophobicity is maintained even when the aerogel composite specimens prepared in the examples and comparative examples are heat-treated at high temperatures, each specimen prepared in Examples 1 to 5 and Comparative Examples 1 to 5 was dried at 200°C for an additional 1 hour under atmospheric pressure, then floated on distilled water at 21±2°C as in 1-1 above, and the results of whether it floated on the distilled water were evaluated, and the results are shown in Table 7 below. Note that in Table 7 below, O indicates the case where the specimen floats on the distilled water, △ indicates the case where the specimen floats inside the distilled water, and X indicates the case where the specimen sinks to the bottom of the water tank.
[0220] division High-temperature hydrophobicity evaluation Example 1 O Example 2 O Example 3 O Example 4 O Example 5 O Comparative Example 1 △ Comparative Example 2 △ Comparative Example 3 X Comparative Example 4 △ Comparative Example 5 X
[0221] As shown in Table 7 above, it was confirmed that the aerogel composites according to the present invention (Examples 1 to 5) all floated on distilled water and maintained their hydrophobicity even after heat treatment at a high temperature. On the other hand, it was confirmed that the specimens of Comparative Examples 3 and 5 did not float on distilled water after heat treatment and all sank to the bottom of the water tank where the test was performed. Although the specimens of Comparative Examples 1, 2, and 4 did not sink to the bottom of the water tank, they sank to about 1 / 3 to 1 / 2 of the depth of the tank from the surface of the distilled water and floated inside the distilled water, indicating that the hydrophobicity of the specimens was not maintained and decreased due to the heat treatment.
[0223] [Experimental Example 4] Evaluation of hydrophobicity of aerogel composite (2)
[0224] To evaluate the surface and internal hydrophobicity of the aerogel composites prepared according to the present invention, the following experiments were performed in accordance with the ASTM C1104 standard. First, specimens measuring 15 cm x 15 cm (thickness approximately 3 mm) were obtained from each of the aerogel composites of Examples 1 to 5 and Comparative Examples 1 to 5, and then dried in an air-circulating oven at 102 to 121 ℃ using a desiccator containing calcium chloride as a drying agent. Subsequently, after storing for 96 hours in an environment of 49 ± 2 ℃ and 95 ± 3% relative humidity, the percentage change in weight of the specimens before and after water vapor absorption was measured as shown in Equation 2 below and expressed as the water vapor absorption rate. The water vapor absorption rate reflects the degree of internal hydrophobicity of the silica aerogel composite. Note that the experimental results for the water vapor absorption rate in Table 8 below are the average values obtained after performing three repeated experiments. The average value was rounded to the first decimal place.
[0225] [Equation 2]
[0226] Water vapor absorption rate (weight%) = {(Weight of specimen after experiment - Weight of specimen before experiment) / (Weight of specimen before experiment)} X 100
[0227] division Water vapor absorption rate (weight%) Example 1 1.1 Example 2 1.8 Example 3 1.2 Example 4 1.1 Example 5 2.4 Comparative Example 1 3.8 Comparative Example 2 3.4 Comparative Example 3 3.9 Comparative Example 4 2.8 Comparative Example 5 3.7
[0228] As shown in Table 8 above, the water vapor absorption rate of the aerogel composites of Examples 1 to 5 was low, approximately 2.5 wt% or less, whereas the water vapor absorption rate of the aerogel composites of Comparative Examples 1 to 5 was at least 2.8 wt% and mostly 3.5 wt% or more. Through this, it was found that the aerogel composite according to the present invention has high surface and internal hydrophobicity and excellent water repellency.
[0230] [Experimental Example 5] Evaluation of Thermal Conductivity of Aerogel Composite
[0231] 1. Measurement of thermal conductivity at room temperature
[0232] To evaluate the room temperature thermal conductivity of the aerogel composite prepared according to the present invention, the room temperature thermal conductivity of the 60 cm x 12 cm aerogel composites prepared in each example and comparative example was measured using a Netzsch HFM436 instrument, and the results are shown in Table 9 below.
[0233] 2. Measurement of high-temperature thermal conductivity
[0234] To evaluate the thermal conductivity at high temperatures, the aerogel composites prepared in the above examples and comparative examples were subjected to GHP (Guarded Hot Plate) high-temperature thermal conductivity measurements at a temperature of approximately 150°C using a GHP 456 instrument from NETZSCH, and the results are shown together in Table 9 below.
[0235] division Room temperature thermal conductivity (mW / mK) High temperature thermal conductivity (mW / mK) Example 1 19 21.9 Example 2 18.3 20.5 Example 3 18.8 20.9 Example 4 17.8 20.2 Example 5 19.1 21.5 Comparative Example 1 22.5 26.4 Comparative Example 2 19.5 24.8 Comparative Example 3 21.8 25.8 Comparative Example 4 20.2 25.3 Comparative Example 5 19.9 24.9
[0236] As shown in Table 9 above, it was found that the aerogel composites according to the present invention (Examples 1 to 5) have lower thermal conductivity and excellent thermal insulation properties at both room temperature and high temperature compared to the aerogel composites of Comparative Examples 1 to 5.
[0238] [Example 6] Manufacture of an insulating member
[0239] An insulating member was manufactured by attaching ALKYN-1505(C) product from ALKYNES, in which a 25 μm thick acrylic adhesive is applied to one side of a 25 μm thick PET film, to both sides of the aerogel composites prepared in Examples 1 to 5 above.
[0241] [Example 7] Manufacture of an insulating member
[0242] An insulating member was manufactured by attaching ALKYN-4005(FR) product from ALKYNES, in which a 25 μm thick acrylic adhesive is applied to one side of a 25 μm thick flame-retardant PET film, to both sides of the aerogel composites prepared in Examples 1 to 5 above.
[0244] [Example 8] Manufacture of an insulating member
[0245] An insulating member was manufactured by attaching an ALKYN-4004D(PS) product from ALKYNES, in which a 7 μm thick polyester film and a 12 μm thick PET film are sequentially laminated on both sides of the aerogel composite prepared in Examples 1 to 5 above, and a 25 μm thick acrylic adhesive is applied to the other side of the polyester film.
[0247] Specific parts of the present invention have been described in detail above. It is evident to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the invention. Accordingly, the actual scope of the invention is defined by the appended claims and their equivalents.
Claims
Claim 1 An aerogel composite comprising a substrate; and an aerogel having a plurality of open pores, wherein the aerogel comprises a plurality of silica aerogel particles, and as a result of performing NMR analysis on the silica aerogel particles using water (H2O) as the saturation fluid, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) is 0.4 x 10⁻⁶ 3 Up to 1.0 X 10 3 Phosphorus, aerogel complex. Claim 2 In claim 1, as a result of performing NMR analysis on the silica aerogel particles using water (H2O) as the saturation fluid, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) is 0.4 X 10 3 Up to 0.9 X 10 3 Phosphorus, aerogel complex. Claim 3 In claim 1, as a result of performing NMR analysis using water (H2O) as the saturation fluid after heat-treating the silica aerogel particles at a temperature of 200 ℃ for 1 hour, the ratio of T1 relaxation time to T2 relaxation time (T1 / T2) is 0.4 X 10 3 Up to 1.0 X 10 3 Phosphorus, aerogel complex. Claim 4 An aerogel composite according to claim 3, wherein the ratio of T1 / T2 to the aerogel particles after heat-treating the silica aerogel particles at a temperature of 200°C for 1 hour is 0.8 to 1.2 times the ratio of T1 / T2 to the silica aerogel particles before heat-treating the silica aerogel particles at a temperature of 200°C for 1 hour. Claim 5 An aerogel composite according to claim 3, wherein the ratio of T1 / T2 to the aerogel particles after heat-treating the silica aerogel particles at a temperature of 200°C for 1 hour is 0.85 to 1.1 times the ratio of T1 / T2 to the silica aerogel particles before heat-treating the silica aerogel particles at a temperature of 200°C for 1 hour. Claim 6 The aerogel composite according to claim 1, wherein the aerogel comprises pores having a pore diameter of 5 to 20 nm in an amount of 25% or less of the pore volume of the aerogel's skeletal structure. Claim 7 In claim 6, the aerogel is an aerogel composite comprising pores having a pore diameter of 5 to 20 nm in an amount of 10% or more and 25% or less of the pore volume of the aerogel's skeletal structure. Claim 8 In claim 1, the aerogel composite is an aerogel composite having a moisture impregnation rate (weight%) represented by the following formula 1 of 4 weight% or less: [Formula 1] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100 In the above formula 1, the weight of the specimen after impregnation refers to the weight of the aerogel composite specimen after impregnating it in distilled water at 21±2 ℃ for 15 minutes, and the aerogel composite specimen has a size of 100 mm X 100 mm in width X length. Claim 9 In claim 1, the aerogel composite is an aerogel composite having a moisture impregnation rate (weight%) represented by the following formula 1 of 3 weight% or less: [Formula 1] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100 In the above formula 1, the weight of the specimen after impregnation refers to the weight of the aerogel composite specimen after impregnating it in distilled water at 21±2 ℃ for 15 minutes, and the aerogel composite specimen has a size of 10 mm X 10 mm in width X length. Claim 10 In claim 8, the aerogel composite having a moisture impregnation rate (weight%) represented by Formula 1 of 10 weight% or less after heat treatment of the aerogel composite at a temperature of 200 ℃ for 1 hour. Claim 11 The aerogel composite of claim 1, wherein the aerogel composite has a water vapor absorption rate of 2.5 weight% or less according to the ASTM C1104 test method. Claim 12 The aerogel composite according to claim 1, wherein the aerogel comprises at least one selected from the group consisting of silica, methylsilylated silica, dimethylsilylated silica, and trimethylsilylated silica. Claim 13 The aerogel composite according to claim 1, wherein the plurality of silica aerogel particles comprises particles in which a plurality of aerogel particles with a particle size greater than 0 and less than or equal to 5 nm are aggregated or bonded. Claim 14 An aerogel composite according to claim 13, wherein the average particle size of the aggregated or bonded aerogel particles is 5 to 2,000 nm. Claim 15 The aerogel composite according to claim 1, wherein the thickness of the aerogel composite is 0.5 to 20 mm. Claim 16 In claim 1, the density of the aerogel composite is 0.05 to 0.50 g / cm³ 3 Phosphorus, aerogel complex. Claim 17 In claim 1, the aerogel composite has a compressive strength of 20 kPa to 80 kPa at 10% strain and a tensile strength of 30 N / cm 2 up to 60 N / cm 2 Aerogel composite that is. Claim 18 An insulating member comprising the aerogel composite of claim 1. Claim 19 In claim 18, the insulating member further comprises a supporting member positioned on at least one of the upper and lower surfaces of the aerogel composite. Claim 20 A battery module comprising a module case having an internal space, one or more battery cells located in the internal space, and an aerogel composite of claim 1 located in the internal space.
Citation Information
Patent Citations
Fire-resistant reinforced aerogel composition
JP2021525699A
Method for preparing aerogel blanket and aerogel blanket prepared by the same
KR1020170104954A
Silica sol, silica aerogel blanket manufactured by using the same and preparing method thereof
KR1020210038374A
Aerogel blanket
KR1020210038375A
Improved hydrophobic aerogel materials
KR1020210126151A
